Self-complementary nickel halides enable multifaceted comparisons of intermolecular halogen bonds: fluoride ligands vs. other halides - Thangavadivale, Vargini (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
The syntheses of three series of complexes designed with self-complementary motifs for formation of halogen bonds between an iodotetrafluorophenyl ligand and a halide ligand at square-planar nickel are reported, allowing structural comparisons of halogen bonding between all four halides C(6)F(4)I···X–Ni (X = F, Cl, Br, I). In the series trans-[NiX(2,3,5,6-C(6)F(4)I)(PEt(3))(2)] 1pX and trans-[NiX(2,3,4,5-C(6)F(4)I)(PEt(3))(2)] (X = F, Cl, Br, I) 1oX, the iodine substituent on the benzene ring was positioned para and ortho to the metal, respectively. The phosphine substituents were varied in the series, trans-[NiX(2,3,5,6-C(6)F(4)I)(PEt(2)Ph)(2)] (X = F, I) 2pX. Crystal structures were obtained for the complete series 1pX, and for 1oF, 1oCl, 1oI and 2pI. All these complexes exhibited halogen bonds in the solid state, of which 1pF exhibited unique characteristics with a linear chain, the shortest halogen bond d(C(6)F(4)I···F–Ni) = 2.655(5) Å and the greatest reduction in halogen bond distance (I···F) compared to the sum of the Bondi van der Waals radii, 23%. The remaining complexes form zig-zag chains of halogen bonds with distances also reduced with respect to the sum of the van der Waals radii. The magnitude of the reductions follow the pattern F > Cl ∼ Br > I, 1pX > 1oX, consistent with the halogen bond strength following the same order. The variation in the I···X–Ni angles is consistent with the anisotropic charge distribution of the halide ligand. The temperature dependence of the X-ray structure of 1pF revealed a reduction in halogen bond distance of 0.055(7) Å on cooling from 240 to 111 K. Comparison of three polymorphs of 1oI shows that the halogen bond geometry may be altered significantly by the crystalline environment. The effect of the halogen bond on the (19)F NMR chemical shift in the solid state is demonstrated by comparison of the magic-angle spinning NMR spectra of 1pF and 1oF with that of a complex incapable of halogen bond formation, trans-[NiF(C(6)F(5))(PEt(3))(2)] 3F. Halogen bonding causes deshielding of δ(iso) in the component of the tensor perpendicular to the nickel coordination plane. The results demonstrate the potential of fluoride ligands for formation of halogen bonds in supramolecular structures.